Mechanisms, Hallmarks, and Implications of Stem Cell Quiescence - Inchul J. Cho; Prudence PokWai Lui; Jana Obajdin; Federica Riccio; Wladislaw Stroukov; Thea Louise Willis; Francesca Spagnoli; Fiona M. Watt (Stem Cell Reports, 2019)
Cellular quiescence is a dormant but reversible cellular state in which cell-cycle entry and proliferation are prevented. Recent studies both in vivo and in vitro demonstrate that quiescence is actively maintained through synergistic interactions between intrinsic and extrinsic signals. Subtypes of adult mammalian stem cells can be maintained in this poised, quiescent state, and subsequently reactivated upon tissue injury to restore homeostasis. However, quiescence can become deregulated in pathological settings. In this review, we discuss the recent advances uncovering intracellular signaling pathways, transcriptional changes, and extracellular cues within the stem cell niche that control induction and exit from quiescence in tissue stem cells. We discuss the implications of quiescence as well as the pharmacological and genetic approaches that are being explored to either induce or prevent quiescence as a therapeutic strategy. : Stem cell quiescence is a dormant but reversible cellular state in which cell-cycle entry and proliferation are prevented. Intrinsic regulators include the cell-cycle machinery, autophagy, chromatin modifiers, and microRNAs. Extrinsic regulators include cell-adhesion molecules and secreted factors. Therapeutic modulation of stem cell quiescence could restore tissue homeostasis. Keywords: stem cells, cancer, quiescence, cell cycle, autophagy, niche, cell therapy